Quantity versus quality of offspring - MELIA, Nadhilla Velda (Institutional Knowledge at Singapore Management University, 2018)
Organisms continually face trade-offs for how to allocate limited energy and resources. One of the key trade-offs involves the quantity versus the quality of offspring. On the one hand, if organisms invest heavily in their offspring to better their developmental and survival outcomes, they tend to only have enough resources to produce a small number of “high-quality” offspring. On the other hand, if organisms make little parental investment per child, they can produce a large number of “low-quality” offspring – although each child has a lower chance of survival, there is a higher probability that at least some offspring will survive long enough to reproduce.